E-024 The Mindframe Capture LP 3 mm and 4 mm thrombectomy device. Early clinical results. (4th July 2012) - Söderman, M; Holmin, S; Andersson, T; Kuntze Söderqvist, Å; Turner, R
Abstract : Introduction: Mechanical thrombectomy is effective in restoring blood flow to the brain in patients with occlusion of large intracranial arteries. Most devices require a 0.021 or 0.027 microcatheter. However, in some instances s smaller microcatheter may be advantageous. We here report the early results with the Mindframe Capture LP 3 mm and 4 mm thrombectomy devices, designed to pass through a 0.010 microcatheter. Material and Methods: 16 patients (8M/8F) with large vessel occlusion and sizeable penumbra were admitted with the intention to treat with thrombectomy using either of the 3 mm or 4 mm Mindframe Capture LP devices. Mean NIHSS was 15. Seven had received previous i.v. rTPA. Technical results: Thrombectomy was unsuccessful because of impossible access in one case, non-embolic occlusion due to vessel dissection in two cases, very old uncooperative patient in one case and device related failure in one case. There were no device related complications. Clinical results are not yet available but will be presented at the meeting. Conclusion: Mindframe Capture LP 3 mm and 4 mm thrombectomy devices are efficient with a low risk for device related complications. Abstract E-024 Table 1 0 1 2a 2b 3 TICI at start 16 TICI final 5 1 1 8 Competing interests: M Söderman: MINDFRAME INC, Rapid medical. S Holmin: None. T Andersson: MINDFRAME INC, Covidien, Stryker, Rapid Medical. Å Kuntze Söderqvist: None. R Turner: MINDFRAME INC.